Stress analysis for a rectangular thick plate of a composite material with a spatially locally curved structure under forced vibration - Akbarov, SD; Tarim, ET (SPRINGER, 2004)
Natural and forced vibrations of a thick rectangular plate fabricated from a composite material with a spatially locally curved structure are investigated with the use of exact three-dimensional equations of motion of the theory, of elastic anisotropic bodies. The investigations are carried out within the framework of the continuum approach developed by Akbarov and Guz'. It is supposed that the plate is clamped at all its edges and is loaded on the upper face with uniformly distributed normal forces periodically changing with time. The influence of the parameters of local curving on the,fundamental frequency of the plate and on the distribution of the normal stress acting in the thickness direction under forced vibration is studied. The corresponding boundary-value problems are solved numerically by employing the three-dimensional FEM modelling.
Keywords: plate; composite material; curved structure; forced vibrations; fundamental frequency; FEM modelling; MECHANICS; Materials Science; Polymer Science